Current Aspects of Antibiotic Therapy of Community-Acquired Pneumonia in Children of Early and Preschool Age (Review) - S.A. Mokiya-Serbina; T.V. Litviniva; A.A. Gordyeyeva (Zaslavsky O.Yu., 2016)
In this article we analyzed current antibiotic resistance of S.pneumoniae. We showed local (region) data on sensitivity of pneumococcus to aminopenicillins, macrolides and cephalosporines traditionally used in schemes of empirical antibiotic therapy of community-acquired pneumonia in children under 5 years. We laid basic principles of rational antibiotic therapy based on the analysis of current national and foreign guidelines on the treatment of community-acquired pneumonia. Insignificant differences in the schemes of empirical antibiotic therapy are marked due to peculiarities of local resistance of S.pneumoniae in different countries. We discussed propriety of some positions of empirical antibiotic therapy in children of early and preschool age.